Analisis Faktor-Faktor Yang Mempengaruhi Penyerapan Tenaga Kerja - Ayi Elsa Nurhasanah; Ari Saptono (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The aim of this research is to see the level of significance of several factors that influence labor absorption in West Java Province, such as investment, minimum wages, economic growth and the Covid-19 pandemic as this research takes data for the period 2017 - 2022. This research uses panel data, namely a combination of time series and cross section data. The research data used is secondary data obtained from the websites of the Indonesian Central Statistics Agency and West Java Province, with a research sample of 19 regencies/cities in West Java Province. The results of this research show that there is a significant simultaneous influence between investment, minimum wages, economic growth and the Covid-19 pandemic on labor absorption in West Java Province 2017-2022. Apart from that, partially, each independent variable also shows a significant influence on labor absorption. Investment and economic growth variables have a positive influence on labor absorption. Meanwhile, the minimum wage has a negative influence on labor absorption in West Java Province.